Utilizing Wordwall and Card Sort Media to Enhance Student Learning Activities in Mawaris Fiqh Material - Nabilah, Farida; Putri, Amanda Deviana; Yanti, Novi Andri; Fadhila, Ririn Nur (LJPI UI Bunga Bangsa Cirebon, 2025)
The lack of student active learning in each school is one of the problems in the world of education. Media that is less attractive, learning methods that are not used appropriately in learning are one of the factors that make students less active or less interactive in the teaching and learning process. In this study, researchers tried to examine how the use of wordwall and card sort media can increase student learning activity. This research was conducted at MAN Sidoarjo with the entire class XI class, totaling 451 students. This type of research uses classroom action research which will be used with pre-cycle and cycle I actions. This research produces that wordwall and card sort media can increase students' learning activity. This can be seen from the percentage carried out in the pre-cycle of 60%, while in cycle I during the implementation of the method the result was a 92% increase in student learning activity